PHOTOPROTECTIVE EFFECTS OF CARRAGEENANS AGAINST ULTRAVIOLETB-INDUCED EXTRACELLULAR MATRIX (ECM) DAMAGE IN KERATINOCYTES - Thevanayagam, Haema; Mohamed, Shar Mariam; Chu, Wan Loy; Zolkapli Eshak (Malaysian Journal of Science, 2022)
Carrageenans, the polysaccharide from red seaweeds is widely used in food, medicine and as an excipient in cosmetics and skincare products. Carrageenans have shown prospective photoprotective effect against ultraviolet B (UVB) irradiation on immortalised normal human keratinocyte (HaCaT) cells. The aim of this research was to evaluate the photoprotective effect of iota (ι), kappa (κ)-carrageenans and their combination with vitamin E against UVB-induced extracellular matrix (ECM) damage in HaCaT cells. The study also assessed the superoxide dismutase (SOD) and catalase (CAT) antioxidant enzymes in UVB exposed pre-treated and non-pre-treated cells. The parameters assessed were biological mediators important for the structural integrity of ECM, comprising of epidermal growth factor receptor (EGFR), mitogen-activated protein kinase (MAPK), activating protein- (AP-1) and matrix metalloproteinases (MMPs), liberated by the UVB exposed cells. Enzyme linked immunosorbent assay was used to evaluate the release of these mediators. Carrageenans enhanced the activities of the antioxidant enzymes SOD and CAT which acts as a defence mechanism against oxidative stress. The levels of the biological mediators were also reduced in cells pre-treated with carrageenans, suggesting that the polysaccharide has potential in maintaining the skin’s integrity by reducing the damage to ECM upon UVB exposure. Taken together, the results suggest that carrageenans do possess photoprotective effects against UVB-induced ECM damage and stimulates antioxidant enzymes.